Characterization of semen collected by pharmacologically induced ejaculation from a stallion with seminal vesiculitis - Cavalero, Thaís Mendes Sanches [UNESP] (2020)
The present study compared the quality of sperm collected by artificial vagina or pharmacologically induced ejaculation from a 10-year-old thoroughbred stallion with seminal vesiculitis. The pharmacological protocol involved intravenous administration of detomidine (0.01 mg/kg) and oxytocin (20 IU) and successfully induced ejaculation in all attempts of semen collection. Sperm motility, plasma membrane and acrosome integrity (PMAI), reactive oxygen species (ROS) levels, polymorphonuclear neutrophil (PMN) percentage, and bacterial profiles of fresh and cooled semen (5°C for 24 hr) were evaluated. Semen obtained by the pharmacological method presented reduced seminal volume, decreased PMN percentage and superior sperm motility in cooled samples. Moreover, higher PMAI and lower ROS levels were observed in semen collected by the pharmacological method. Therefore, pharmacologically induced ejaculation is an alternative to obtain semen with minimal contamination and with sperm of superior quality and longevity from stallions with seminal vesiculitis.